Blunt abdominal trauma leading to acute abdominal wall hernia: a case report - Sharma, D; Shrestha, Santosh; Ghimire, R (Nepal Journal of Medical Sciences, 2020)
Acute traumatic abdominal wall hernia is a rare but serious diagnosis resulting from blunt abdominal trauma. The challenge of managing acute traumatic abdominal hernia is approach and timing of repair. We describe a 32 years male patient’s acute traumatic abdominal wall hernia and its management.